Peningkatan Kapasitas Pelaku Fashion Melalui Pelatihan E-Commerce pada UMKM “Amanah Jaya” di Pasar Tambelang, Kabupaten Bekasi - M. Risky Yazid; Novi Fitria Hermiawati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Entrepreneurship is the process of identifying, developing and bringing a vision to life. This vision can be in the form of innovative ideas, sales ideas, opportunities, better ways of doing things. MSMEs have an important role in national economic growth, including the fast-growing fashion sector. However, the use of digital technology by MSMEs is still limited, especially in terms of marketing via e-commerce. This activity aims to increase the capacity of fashion players in the "Amanah Jaya" MSMEs at Tambelang Market, Bekasi Regency through e-commerce training. The method used is participatory training with a direct practical approach using the lecture method where the resource person conveys information orally to the participants. The results of the activity showed that participants experienced increased understanding and skills in managing online stores, such as writing product descriptions to order management. Apart from that, there is a change in the attitude of business actors who are more open to the use of digital technology in running business. This e-commerce training is effective in increasing the capacity of MSME players in the fashion sector and is able to encourage technological adaptation to increase business competitiveness in a sustainable manner.